User satisfaction and dissatisfaction with learning management system in post-adoption stage : critical incident technique (CIT) approach - Awang Najib, Awang Mohamad (Universiti Malaysia Sarawak, (UNIMAS), 2014)
This study investigates on the user satisfaction and dissatisfaction with moodle Learning Management System (LMS) known as Morpheus at Universiti Malaysia Sarawak (UNIMAS) during post-adoption stage among postgraduate students of Master of Science (Learning Sciences), Faculty of Cognitive Sciences and Human Development (FCSHD). Critical incident technique (CIT) approach is used to collect data for analysis in order to extend our understanding and to clarify on possible sources of satisfaction and dissatisfaction among users.